PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KUALITAS AUDIT (Studi Empiris pada Perusahaan BUMN dan BUMD yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Adinda Fahrani Annabila; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2026)
This study examines the effect of audit committee characteristics, namely professional expertise, committee size, meeting frequency, and gender diversity, on audit quality in State-Owned Enterprises (BUMN) and Regional-Owned Enterprises (BUMD) listed on the Indonesia Stock Exchange during 2020–2024. Audit quality is measured using audit fees and Big Four auditor affiliation as proxies. This study employs a quantitative approach using secondary data obtained from annual reports and financial statements. A total of 115 firm-year observations were selected through purposive sampling. Data were analyzed using multiple linear regression and logistic regression. The findings reveal that audit committee size has a positive and significant effect on audit quality measured by Big Four auditor affiliation, while audit committee meeting frequency positively and significantly affects audit quality measured by audit fees. However, professional expertise and gender diversity of the audit committee do not significantly influence audit quality. These results suggest that the effectiveness of audit committee oversight is more strongly reflected in committee size and meeting intensity than in other audit committee characteristics. The study contributes to the literature on corporate governance by providing evidence from BUMN and BUMD in Indonesia.